Sistemas de Abastecimiento de Agua en la Zona Indígena Cabécar-Chirripó - Araya-Obando, Andrés (Instituto Tecnológico de Costa Rica, 2007)
This project consists on the design of water supply systems in the indigenous zone Chirripó-Cabécar. Within the objectives of this project it is to put in practice appropriate alternative technologies. Has is for aqueducts design for difficult access zones, determine the list of materials along with the capital costs of the water supply system and the construction blue prints. User guides were developed, with the purpose of stimulating the indigenous community to participate in the construction, operation and maintenance of the water supply system. More attention must be render to these distant communities, more projects must be developed on their benefit and a call upon the institutions implicated must be done so they do a reorganization of their procedures and standards in order to obtain viable proposals for the indigenous zone.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción). Instituto Tecnológico de Costa Rica; Escuela de Ingeniería en Construcción, 2007.
Keywords: Agua potable; Diseño de acueductos; Guiía de mantenimiento; Polietileno; Sistema de tratamiento